2017
DOI: 10.1002/jmri.25901
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted MRI and intravoxel incoherent motion model for diagnosis of pediatric solid abdominal tumors

Abstract: BackgroundPediatric retroperitoneal tumors in the renal bed are often large and heterogeneous, and their diagnosis based on conventional imaging alone is not possible. More advanced imaging methods, such as diffusion‐weighted (DW) MRI and the use of intravoxel incoherent motion (IVIM), have the potential to provide additional biomarkers that could facilitate their noninvasive diagnosis.PurposeTo assess the use of an IVIM model for diagnosis of childhood malignant abdominal tumors and discrimination of benign f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…D mean and D dark measurements of diffusion coefficient D also resulted in high levels of diagnostic accuracy, confirming previous results for the IVIM model in other entities. 21 The diagnostic performance of ADC-derived values was similar to that of IVIM-derived values with high levels of sensitivity (ADC mean 92%; D mean 92%) and specificity (ADC mean 98%; D mean 98%).…”
Section: Well Et Al Diffusion-weighted Imaging In Nf1mentioning
confidence: 60%
See 1 more Smart Citation
“…D mean and D dark measurements of diffusion coefficient D also resulted in high levels of diagnostic accuracy, confirming previous results for the IVIM model in other entities. 21 The diagnostic performance of ADC-derived values was similar to that of IVIM-derived values with high levels of sensitivity (ADC mean 92%; D mean 92%) and specificity (ADC mean 98%; D mean 98%).…”
Section: Well Et Al Diffusion-weighted Imaging In Nf1mentioning
confidence: 60%
“…By contrast, the biexponential intravoxel incoherent motion (IVIM) model enables further separation of tissue perfusion and diffusivity. 19,20 IVIM has shown promise for distinguishing malignant from benign pediatric abdominal tumors 21 and in the differentiation of high-from low-grade hepatocellular carcinoma. 22 Therefore, we aimed to assess the value of DW MRI for characterization of benign and malignant PNSTs in patients with NF1, and to compare the diagnostic performance of biexponential IVIM with that of monoexponential data analysis and established morphological features of malignant transformation.…”
Section: Neuro-oncologymentioning
confidence: 99%
“…As noted above, MRI is an attractive option because it offers improved spatial resolution and lack of ionizing radiation exposure ( 25 ). When examining multiparametric MRI data from pediatric patients with abdominal lesions, Meeus et al ( 26 ) were able to use apparent diffusion coefficient (ADC) mapping and the intravoxel incoherent motion (IVIM) model to distinguish between different abdominal tumor histologic types. Not only could MRI discriminate between benign and malignant tumors, it also was able to specifically identify WT apart from neuroblastomas based on diffusion and perfusion characteristics.…”
Section: Wtmentioning
confidence: 99%
“…MRI-based radiomics has value in the diagnosis and differential diagnosis of posterior fossa tumors in children (15)(16)(17). With regard to radiomics of children's abdominal tumors, at present, there is only one study (18), which found that histogram parameters (90th percentile of D *, mean value of f, etc.) based on MRI with intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) can help to distinguish retroperitoneal neuroblastoma from nephroblastoma in children.…”
Section: Introductionmentioning
confidence: 99%